PERBEDAAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF THINK PAIR SHARE (TPS) DENGAN MODEL PEMBELAJARAN INQUIRY SMK SWASTA AR RAHMAN MEDAN KELAS X - Ari Fadilla; Dalmi Iskandar Sultani (Sekolah Tinggi Pariwisata Mataram, 2022)
Research title: Differences in student learning outcomes using the Think Pair Share (TPS) cooperative learning model with the Inquiry learning model at AR Rahman Private Vocational School, Medan TA. 2021/2022. The purpose of the study was to determine the difference between the use of the Think Pair Share (TPS) cooperative learning model and the inquiry model on economic learning outcomes. The research method uses Post-test Only Control Design. The population in this study were all students of class X OTKP Private Vocational School AR Rahman Medan. The sample of this research is class X totaling 30 students. The research instrument used was interviews, tests, and documentation. The results showed that the value of tcount is smaller than ttable, where tcount = 0.39 < ttable = 1.671. Thus, H0 is rejected and Ha is accepted = rhyme. Conclusion: there are differences in the use of the Think Pair Share (TPS) cooperative learning model with the Inquiry learning model. Against student business economics learning outcomes.